2016
DOI: 10.1002/jpln.201600076
|View full text |Cite
|
Sign up to set email alerts
|

The chemical nature of organic phosphorus that accumulates in fertilized soils of a temperate pasture as determined by solution 31P NMR spectroscopy

Abstract: Inefficiency of fertilizer phosphorus (P) use in grazing systems is often associated with the accumulation of inorganic and organic P in fertilized soil. However, the chemical nature of the accumulated organic P remains poorly understood. The aim of this study was to use solution 31P nuclear magnetic resonance (NMR) spectroscopy on sodium hydroxide–ethylenediaminetetraacetic acid (NaOH‐EDTA) extracts to identify the chemical nature of organic P in soils from a medium‐term (13 years) permanent pasture field exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 72 publications
(163 reference statements)
0
15
0
Order By: Relevance
“…Whilst there is much research on the mechanisms associated with specific biomolecules of organic P, particularly that of myo-IHP (Turner et al, 2002), there is limited insight on the mechanisms governing pools of organic P as the broad signal in a NMR spectrum. There is supporting evidence to suggest their sequestration is related to factors affecting plant growth, soil organic matter and climate, which involve slow and soil-based mechanisms (Doolette et al, 2017;McLaren et al, 2017;Schefe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there is much research on the mechanisms associated with specific biomolecules of organic P, particularly that of myo-IHP (Turner et al, 2002), there is limited insight on the mechanisms governing pools of organic P as the broad signal in a NMR spectrum. There is supporting evidence to suggest their sequestration is related to factors affecting plant growth, soil organic matter and climate, which involve slow and soil-based mechanisms (Doolette et al, 2017;McLaren et al, 2017;Schefe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Other unidentified peaks in the monoester region were grouped into the Monoester 1 (Mono1, 7.0-6.0 ppm), Monoester 2 (Mono2; peaks not specifically identified between 5.9 and 3.8 ppm), and Monoester 3 (Mono3, 3.2-2.5 ppm). The broad peak detected by others in the monoester region would be included in the Mono2 category (e.g., McLaren et al 2016). Others unknown peaks were detected in the diester region and divided into other diester 1 (Di1, 2.5 Fig.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…They reported an accumulation of P i and inositol phosphate in the top 5 cm soil depth. Results from studies carried out in P-fertilized grasslands in Netherlands over 11 yr (Koopmans et al 2003), and in Australia for 13 yr (McLaren et al 2016) revealed increased P i concentrations in the top 5 cm and increased orthophosphate monoesters in the top 10 cm soil depths, respectively. In Northern Ireland, high rates of P fertilization increased the concentrations of orthophosphate and total P i , and decreased the concentrations of total inositol hexaphosphate (IHP).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to environmental risk zones, controlled-release P fertilizers offer the potential to reduce runoff losses [93] . In terms of chemical form, many studies have focused on organic P fertilizers [94] , chelates and polymers. One study has also shown that based on temperature and pH controlled-release rates, targeted P fertilizers are a promising new direction [95] .…”
Section: Phosphorus Recycling In the Whole Chainmentioning
confidence: 99%